Use of alpha-amylase and amyloglucosidase combinations to minimize the bread quality problems caused by high levels of damaged starch - Barrera, Gabriela (2016)
The objective of this work was to investigate the contribution of α-amylase and amyloglucosidase to dough fermentation process and bread quality, as an alternative to reduce the negative effects caused by high damaged starch in flour. The dough properties during the proofing process were modified by higher damaged starch content. Higher damaged starch in flour resulted into breads with darker crusts and firmer crumbs. The enzymes reduced the negative influence of damaged starch, producing a positive effect on the maximum carbon dioxide pressure reached during fermentation and the carbon dioxide volume retained by dough. Incorporation of alpha-amylase reduced dimension ratio and crumb firmness attributes; however, progressive additions of this additive produced lower bread volume and red intensity, and higher crumb firmness. The amyloglucosidase additions produced higher bread volume and red intensity of the crust, and lower brightness crust and gas cell diameter. Incorporation of amyloglucosidase was beneficial in the presence of a suitable quantity of damaged starch. The results confirmed that the α-amylase and amyloglucosidase additions significantly improved bread quality. Incorporation of α-amylase and amyloglucosidase led to higher bread loaves and lower crumb firmness throughout the storage period, promoting a longer life of the finished product.